RANS Simulation of the Effect of Pulse Form on Fluid Flow and Convective Heat Transfer in an Intermittent Round Jet Impingement - M. A. Pakhomov; V. I. Terekhov (Energies, 2020)
The of effect pulse form (rectangular, sinusoidal and triangular) on the fluid flow and heat transfer of an intermittent jet impingement was studied numerically. It was shown in a non-steady-state jet, both an increase and decrease in heat transfer are possible compared with steady-state jet for all investigated pulse forms. For small distances between the pipe edge and obstacle (H/D ≤ 6) in the pulsed jet, heat transfer around the stagnation point increases with increasing pulse frequency, while for H/D > 8 an increase in frequency causes a heat transfer decrease. A growth in the Reynolds number causes a decrease in heat transfer, and data for all frequencies approach the steady-state flow regime. The numerical model is compared with the experimental results. Satisfactory agreement on the influence of the form and frequency of pulses on heat transfer for the pulsed jet on the obstacle surface is obtained.